Scattering of a flat top solitons of cubic - quintic nonlinear Shrödinger equation by a linear delta potential - Umarov, Bakhram A.; Mohd Busul Aklan, Nor Amirah (IOP Publishing, 2017)
The flat top soliton is a localized solution of cubic - quintic Nonlinear Shr¨odinger equation (C-Q NLSE) that can propagate preserving its shape. In this work we consider the interaction of soliton with weak external localized potentials. It is shown that depending on an initial velocity the soliton may be reflected or transmitted by potential. The approximate analytical results based on varational approach qualitatively confirmed by numerical simulations.